Verbal Interaction of Professional and Peer Led Group Counselling Sessions - Guttman, Mary Alice Julius (Canadian Journal of Counselling and Psychotherapy, 2011)
Four counsellors were randomly assigned to lead four counselling groups for the duration of eight sessions during a three-day retreat of an adolescent student organization. Counsellors were classified into two groups according to their counselling status: professional and peer. An analysis of the verbal interactions of the sessions between groups indicates significant differences on the Hill Interaction Matrix HIM-G measures. Groups led by professional counsellors were more therapeutic, risk oriented, work oriented and less socially oriented than groups led by peer counsellors.